The strategies of the new school of urban banditry in Cameroon: accounts of the tempted and the victims as a call to vigilance - Emmanuel Dekane (Technium Social Sciences Journal, 2021)
All over the world and on all fronts, the Information and Communication Technologies have revolutionized human behavior. In the area of urban banditry, cell phones are used by bandits to devise intricate and sophisticated operating modes. This work both looks at the new operating modes of urban bandits and the role cell phones play in the development of this new school of crime. These study is based on the assumption that cell phones have provided bandits with a new modus operandi. The hypothesis was validated, from the surveys and interviews conducted with gendarmes, police officers, taxi drivers, traders and people who have been victims of the bandits as they were moved around town. The results show that the bandits use mobile phones to scam, spy and ambush through various aphorisms. This article presents urban bandits’ new operating formulas which were revealed through oral information and the accounts of victims. Written following the interpretative phenomenology theory, it calls on citizens to be more prudent as they move around the city.